A COMPARATIVE STUDY OF RIGHT TO EDUCATION ACROSS VARIOUS JURISDICTIONS - Kumar, Anjay; Pandey, Ujjaval (ShodhKosh: Journal of Visual and Performing Arts, 2024)
For a developing society there needs awareness and literacy among people about various aspects of the contemporary world. Every society wants to have civilized and law-abiding citizens for multidirectional growth. In achieving all these objectives education and upbringing of a person plays an important role. International organizations also provide Right to education (RTE) to persons. Various international statutes also provide for RTE and its enforcement. Countries have created setup of a system to provide free education up to a certain level to its citizens. Every country has its own framework for enforcement of RTE depending upon various socio-cultural conditions. There is similarity in most of the developing and developed countries which follow a system that provides basic and compulsory education to all students on governments expenses and bear expenses of education above it as per their capacity. In this study we would cover the application and other factors related to RTE specially of United Kingdom, United States, China and India. The study also tries to find-out the challenges in enforcing the RTE. The study will also try to developments in enforcement of RTE in international law and these targeting countries.